DIVERSIFIKASI PRODUK OLAHAN BERBASIS IKAN PATIN SEBAGAI PRODUK UNGGULAN BUMDES DI DESA SUNGAI SORIK KABUPATEN KUANTAN SINGINGI - Dewita, Dewita; Thamrin, Thamrin; Sukendi, Sukendi; Syahrul, Syahrul; Sidauruk, Shanty W (Fakultas Perikanan dan Kelautan Universitas Riau, 2022)
Sungai Sorik Village is one of the villages in the Kuantan Hilir Seberang District, Kuantan Singingi Regency (Kuansing). In this village there is a Village-Owned Enterprise (BUMDES) whose members are young women who manage the Sorik River Tourism Lake. This Lake Wisata is visited by residents around the sub-district and even residents of other sub-districts from both Kuansing district and neighboring districts, namely INHU district (Rengat). Culinary tourism is an innovative effort to support tourism activities that provide superior food as an attraction for tourists. For this reason, to produce protein-rich snack foods, dragon leg nuggets and brains are made from fish raw, especially catfish. The purpose of this community service activity in Sungai Sorik Village is to develop BUMDES to produce protein-rich snack foods as a form of creative economy which is carried out by making flavor variants of snack food products. The result of implementing community service activities in developing BUMDES is a new taste of fish-based snack food products. Based on consumer interest in the resulting flavor variant products, it turns out that all the variants produced are preferred by consumers.